Answer:
The Pythagorean theorem deals with the lengths of the sides of a right triangle. ... The sum of the squares of the lengths of the legs of a right triangle ('a' and 'b' in the triangle shown below) is equal to the square of the length of the hypotenuse ('c').
Step-by-step explanation:
The only thing that you should do is to put 1, 2, 3, and 4 instead of the n and then you will get the first four terms!
f(1) = 4(1) - 2 = 2
f(2) = 4(2) - 2 = 6
f(3) = 4(3) - 2 = 10
f(4) = 4(4) - 2 = 14
Have a great day!
Answer:
i need a bad bleep
Step-by-step explanation:
lol
Answer:
1) (-6,-9)
times the top equation buy -4 so you cancel out the y
so it be -8x+4y=12 no cancel out the y's
so it be -8x=12 and 5x=6
now combined like terms to get -3x= 36
x = -6 now go plug that back in one of the equations to get y
y = -9
2) (-2,-5)
now on this one you going to substitute y= (2x-1) for y in the otheir eqaution
so it look like 3x-(2x-1)=-1
do your combining of like terms and your division & you get x = -2
now plug x in to y=2x-1 to get y = -5
The answer is: Each bag of flour weighs 1,32 kg.
If we the total weight of the bags is given, and we know both the number of bags of flour and sugar, and we also know the weight of each bag of sugar, then we have to find the unknown, which is X. 30 times X plus 4 times the weight of a bag of sugar would equal 42.6kg. Next step is to put the unknown on one side and the known values on the other side. We have 30 times X equals 42.6 minus 4 times 0.75.
To find X we need to divide the value with 30, or to sum up
30X + 4*0.75 = 42.6
30X + 3 = 42.6
X = (42.6 - 3) / 30
X = 1.32 kg